Intrathoracic migration of I-125 seed marker following ultrasound-guided lymph node localization in locally advanced breast cancer: a case report - Coco Smit; Thomas E. van der Krieken; Maikel T. H. Brauer; Fleur J. W. Mauritz; Thomas Schok (Discover Oncology)
Abstract Iodine-125 (I-125) seed markers are commonly used in breast cancer surgery for precise tumor localization; however, it is extremely rare for an I-125 seed to migrate. This case report highlights a previously undocumented occurrence of intrathoracic migration of an I-125 seed after ultrasound guided marking of a lymph node in a patient with locally advanced breast cancer.